Bioelectrical Impedance Spectroscopy (BIS) For Ratiometric Identification - Alhaq, Elmira Rofida; Salwa, Umaimah Mitssalia Umi; Ain, Khusnul; Sapuan, Imam (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
This research explores the potential use of Electrical Impedance Spectroscopy (EIS) and ratiometric methods to improve security and reproducibility in bioelectrical impedance-based biometric authentication systems. Traditional biometric technologies such as fingerprints are susceptible to forgery and less effective in handling external variations, making bioelectric signal-based approaches a promising alternative. By using Analog Discovery 2 to measure the impedance of ten pairs of fingers in the frequency range of 20 kHz to 500 kHz, with a 1 mA sinusoidal current injected into the subject's fingers, real-time data collection can be performed with the precision required for biometric applications. The measurement results show that the impedance value for each finger differs among subjects, making it a useful parameter for biometric authentication. The application of the ratiometric method successfully reduces day-to-day measurement variations, especially at high frequencies above 100 kHz, resulting in more stable and consistent data. This research shows that bioelectrical impedance methods have the potential to improve security compared to traditional methods such as fingerprinting, as they are more difficult to replicate. This approach offers a promising solution for a more secure and highly reproducible biometric authentication system, with potential applications in various security systems and wearable technologies.